SAFETY OF HOSPITALIZED ELDERLY PATIENTS: AN INTEGRATIVE LITERATURE REVIEW - Thayane Dias dos Santos; Fátima Helena do Espírito Santo; Karinne Cristinne da Silva Cunha; Carla Lube de Pinho Chibante (Universidade Federal do Paraná, 2016)
The objective was to identify how the safety of hospitalized elderly patients has been discussed in the scientific literature. An integrative literature review was undertaken in the databases Literatura Latino Americana e do Caribe em Ciências da Saúde, Scientific Electronic Library Online, Medical Literature Analysis and Retrieval System and U.S. National Library of Medicine, published between 2009 and 2015. The 25 selected publications discuss the importance of promoting affective care in the reduction of insecurity and adverse events in hospitalized elderly, besides the challenges for the implementation of a safe and high-quality environment for these patients. Gaps were found in the knowledge on this theme. Further studies are needed that focus on the description of a dimensioned and suitable environment and on the elaboration and implementation of care quality safety and improvement programs for elderly patients while in hospital.